Amorphous low temperature resistant polyester composition and method of making
Patent Information
- Application Number
- CN202311310958.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-10-10
AI Technical Summary
[0009]本发明是针对现有技术存在的缺陷提供一种非晶型耐低温聚酯组合物,解决现有PET制品低温使用环境中脆性大,极易发生破裂的问题
[0035] This invention achieves a rational alternation of different soft/hard molecular chains through copolymerization and links between different molecular chains through crosslinking, resulting in an amorphous, low-temperature resistant polyester composition. Products prepared from this composition exhibit non-crystallization, good transparency, and excellent low-temperature resistance. Compared with conventional PET of the same intrinsic viscosity at low temperatures, the impact strength of the sample is increased by more than 3 times, and the elongation at break is increased by more than 5 times. This solves the problem of high brittleness and easy breakage of existing PET products in low-temperature environments. It broadens the application fields and usage areas of PET and has great market potential.
Smart Images

Figure BDA0004487763520000021 
Figure BDA0004487763520000022 
Figure BDA0004487763520000023
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyester, specifically relating to an amorphous low-temperature resistant polyester composition and its preparation method. Background Technology
[0002] Polyethylene terephthalate (PET) is a semi-crystalline polymer with excellent optical properties and weather resistance. Amorphous PET plastic exhibits good optical transparency. Furthermore, PET plastic possesses excellent abrasion resistance, dimensional stability, and electrical insulation. Bottles made from PET are widely used due to their high strength, good transparency, non-toxicity, impermeability, light weight, and high production efficiency.
[0003] However, PET is mainly composed of benzene rings, exhibiting high rigidity and a glass transition temperature (Tg) of 78–80℃. The lower the ambient temperature of PET products, the greater the material's brittleness, making it prone to breakage and posing safety hazards. At room temperature, the impact strength of standard PET samples is approximately 50–60 J / m, while at -20℃, it falls below 20 J / m. This limitation restricts PET's performance in low-temperature environments. Therefore, modifying PET to improve its low-temperature resistance is of significant practical importance in expanding its application areas and usage regions.
[0004] Chinese patent CN108034204A discloses a low-temperature impact-resistant polyester composition and its preparation method. This low-temperature impact-resistant polyester composition is composed of the following raw materials: PBT resin, POK, TPEE elastomer, MBS toughening agent, compatibilizer, transesterification inhibitor, antioxidant, and lubricant, etc., and the composition is prepared by twin-screw blending.
[0005] Chinese Patent CN103042780A discloses a low-temperature resistant biaxially oriented polyester film and its preparation method. The polyester film includes a substrate layer, with low-temperature resistant layers disposed on both sides of the substrate layer; the low-temperature resistant layers comprise 20-60% polyester material, 20-60% thermoplastic elastomer, and 5-20% low-temperature toughening composition.
[0006] Chinese patent CN105255149A discloses a low-temperature toughened reinforced PC / PBT alloy material and its preparation method, which improves the low-temperature impact performance of the alloy by adding a low-temperature toughening agent. However, it does not disclose the impact performance and heat resistance of the alloy material at room temperature. In addition, the PC content is about 50%, resulting in excessively high manufacturing costs for the alloy.
[0007] Chinese Patent CN1020939545A discloses a method for preparing elastomers based on 2-methyl-1,3-propanediol terephthalate and its copolyester. The method involves esterification of a specific diacid and a diol, followed by the addition of a polyether glycol, and then compression polymerization to obtain an elastomer based on 2-methyl-1,3-propanediol terephthalate and its copolyester.
[0008] Existing patents primarily improve the impact resistance and low-temperature resistance of polyester matrices by blending or copolymerizing POK, TPEE elastomers, MBS toughening agents, low-temperature toughening compositions, polyether glycols, and PC into PET or PBT matrices. However, the addition of POK, TPEE elastomers, MBS toughening agents, and PC to these solutions all suffer from poor compatibility with the polyester matrix, affecting product transparency and increasing costs. Furthermore, even after the polyester molecular chains are stretched and oriented, the intermolecular forces perpendicular to the orientation direction remain weak, posing a continued risk of product breakage. Summary of the Invention
[0009] This invention addresses the shortcomings of existing technologies by providing an amorphous, low-temperature resistant polyester composition, thus solving the problem of high brittleness and easy breakage of existing PET products in low-temperature environments. This invention achieves a rational alternation of different soft / hard molecular chains through copolymerization and establishes molecular chain links between different chains through crosslinking reactions, resulting in an amorphous, low-temperature resistant polyester composition. Products prepared from this composition exhibit characteristics such as non-crystallization, good transparency, and excellent low-temperature resistance.
[0010] The objective of this invention can be achieved through the following technical solutions:
[0011] An amorphous low-temperature resistant polyester composition, the structural formula of which is as follows:
[0012] R1
[0013]
[0014] Among them, R2, R3 and R4 are independently selected from structural unit A, structural unit B or OH;
[0015] Structural Unit A:
[0016]
[0017] B structural unit:
[0018]
[0019] Wherein: n1 structural unit quantity: 10~25; n2 structural unit quantity: 75~90.
[0020] A method for preparing the above-mentioned amorphous low-temperature resistant polyester composition, comprising the following steps:
[0021] The composition comprises amorphous component A and amorphous component B. The monomers of amorphous component A are diacid a and diol a, which are prepared by esterification and polycondensation under the action of a catalyst. The monomers of amorphous component B are diacid b and diol b, which are prepared by esterification and polycondensation under the action of a catalyst using a polyol as a branching agent. Amorphous component A is added during the polycondensation reaction. After the reaction is completed, the mixture is cooled and granulated to obtain an amorphous low-temperature resistant polyester composition masterbatch.
[0022] In the technical solution of this invention: in the amorphous component A, the dicarboxylic acid a is a mixture of purified terephthalic acid and isophthalic acid, the diol a is 1,4-butanediol, and the catalyst is antimony glycol ethylene glycol, tetrabutyl titanate, or germanium dioxide.
[0023] In the technical solution of this invention: in amorphous component A, the amount of metal element in the catalyst is 50-200 μg / g.
[0024] In the technical solution of this invention, isophthalic acid accounts for 20-30% of component A.
[0025] In the technical solution of this invention, in the amorphous component B, the dicarboxylic acid b is purified terephthalic acid, and the diol b is one or more of ethylene glycol, phenylethylene glycol, pentaerythritol, 1,4-cyclohexanediethanol, and spirodiol; the branching agent is at least one of glycerol, pentaerythritol, and trimethylolpropane; and the catalyst is antimony glycolide, tetrabutyl titanate, or germanium dioxide. Further preferably, the diol b is ethylene glycol, phenylethylene glycol, and pentaerythritol; or the diol b is ethylene glycol, phenylethylene glycol, and glycerol; or the diol b is ethylene glycol, phenylethylene glycol, 1,4-cyclohexanediethanol, and trimethylolpropane; or the diol b is ethylene glycol, phenylethylene glycol, and trimethylolpropane.
[0026] In the technical solution of this invention: the amount of catalyst metal element in amorphous component B is 5-200 μg / g.
[0027] In the technical solution of this invention: in the amorphous component B, the diol b is phenylethylene glycol, and phenylethylene glycol accounts for 15-30% of component B.
[0028] In the technical solution of this invention: amorphous component B accounts for 75-90% of the amorphous low-temperature resistant polyester composition.
[0029] In the technical solution of this invention, when the intrinsic viscosity of the polycondensation reaction is 0.65 to 0.85 dL / g, amorphous component A is added.
[0030] In the technical solution of this invention: the benzene ring structure of purified terephthalic acid and phenylethylene glycol is used to form an amorphous rigid structural unit of copolyester. The benzene ring of phenylethylene glycol is located on the side of the molecular chain, which increases the spacing between local molecular chains and increases the "vacuum" between molecular chains, providing buffer space for the slippage of molecular chains. Even in low temperature environments, the impact resistance of the composition can be increased.
[0031] In this invention, purified terephthalic acid, isophthalic acid, and 1,4-butanediol are used to form an amorphous flexible structural unit, which lowers the energy barrier for local molecular chain movement in low-temperature environments (e.g., Figure 1 As shown in the figure, the "energy absorption" effect is achieved through deformation.
[0032] In the technical solution of this invention: by using amorphous design, the crystallization ability of PET is reduced, the entanglement between molecular chains is increased, the defect of insufficient inter-molecular forces is solved, and the transparency of the product is improved.
[0033] In this invention, a branching agent is used to connect different linear molecular chains, increasing the intermolecular forces and further compensating for the low intermolecular forces of linear polymers (e.g., ...). Figure 1 , Figure 2 ).
[0034] The beneficial effects of this invention are:
[0035] This invention achieves a rational alternation of different soft / hard molecular chains through copolymerization and links between different molecular chains through crosslinking, resulting in an amorphous, low-temperature resistant polyester composition. Products prepared from this composition exhibit non-crystallization, good transparency, and excellent low-temperature resistance. Compared with conventional PET of the same intrinsic viscosity at low temperatures, the impact strength of the sample is increased by more than 3 times, and the elongation at break is increased by more than 5 times. This solves the problem of high brittleness and easy breakage of existing PET products in low-temperature environments. It broadens the application fields and usage areas of PET and has great market potential. Attached Figure Description
[0036] Figure 1 A schematic diagram showing the direction of rupture in a typical PET product.
[0037] Figure 2 Example 1: Schematic diagram of the arrangement of amorphous low-temperature resistant molecular chains.
[0038] Note: The arrows indicate the direction of force, which is perpendicular to the direction of molecular chain alignment, i.e., the direction in which the product is prone to breakage. Detailed Implementation
[0039] The present invention will be further described below with reference to embodiments, but the scope of protection of the present invention is not limited thereto:
[0040] Comparative Example 1:
[0041] In a polyester reactor, 350g of purified terephthalic acid, 209g of ethylene glycol, 200μg / g of antimony glycolate, and 50μg / g of sodium acetate were mixed to form a slurry and added to an esterification reactor. The esterification reaction temperature was 220-260℃. After the esterification reaction, the mixture was transferred to a final condensation reactor for polycondensation reaction at a temperature of 275-285℃. After the polymerization reaction was completed, the melt was cooled and granulated to obtain a particle intrinsic viscosity of 0.80 dL / g, in accordance with the polyester testing standard (GB17931-2003).
[0042] Comparative Example 2:
[0043] (1) Mix 267.5g of purified terephthalic acid, 132.5g of isophthalic acid (accounting for 25% of the total polyester), 400g of 1,4-butanediol, and 50μg / g of tetrabutyl titanate (calculated as titanium element) and slurry them. Add the mixture to the reaction vessel. The esterification reaction temperature is 220-240℃. After the esterification reaction, the mixture is put into the final condensation vessel for polycondensation reaction. The polycondensation temperature is 250-260℃. After reaching the predetermined reaction endpoint, the melt is cooled and granulated to obtain the intrinsic viscosity of chips: 0.80dL / g.
[0044] (2) Mix 400g of purified terephthalic acid, 240g of ethylene glycol, 500μg / g of glycerol, and 150μg / g of antimony glycol (calculated as antimony element) and slurry them. Add the mixture to the reactor. The esterification reaction temperature is 220-260℃. After the esterification reaction, the mixture is transferred to the final condensation reactor for polycondensation reaction at a temperature of 270-285℃. When the intrinsic viscosity of the melt reaches 0.88dL / g, add the chips from step 1 to the reactor at a mass ratio of 25%. Continue the reaction for 0.5 hours, cool the melt, and granulate it to obtain amorphous low-temperature resistant composite chips with an intrinsic viscosity of 0.90dL / g.
[0045] Example 1:
[0046] (1) Mix 294g of purified terephthalic acid, 106g of isophthalic acid (accounting for 20% of the total polyester), 400g of 1,4-butanediol, and 200μg / g of tetrabutyl titanate (calculated as titanium element) and slurry them. Add the mixture to the reaction vessel. The esterification reaction temperature is 220-260℃. After the esterification reaction, the mixture is transferred to the final condensation vessel for polycondensation reaction. The polycondensation temperature is 255-265℃. After reaching the predetermined reaction endpoint, the melt is cooled and granulated to obtain a chip intrinsic viscosity of 0.80dL / g. The polymer structure is recorded as structural formula 1, and the number average molecular weight is 34528.
[0047] (2) Mix 400g of purified terephthalic acid, 240g of ethylene glycol, 138.6g of phenyl ethylene glycol (accounting for 30% of the total polyester), pentaerythritol, and 200μg / g of antimony glycol (calculated as antimony element) and slurry them. Add the mixture to the reactor. The esterification reaction temperature is 220-260℃. After the esterification reaction, the mixture is transferred to the final condensation reactor for polycondensation reaction. The polycondensation temperature is 270-285℃. When the intrinsic viscosity of the melt reaches 0.65dL / g, the polymer structure is obtained and is recorded as structural formula 2. The number average molecular weight is 20175. Add the chips from step 1 to the reactor at a mass ratio of 10%. Continue the reaction for 0.5 hours. Cool the melt and granulate it to obtain amorphous low-temperature resistant composite chips with an intrinsic viscosity of 0.70dL / g and a number average molecular weight of 29525.
[0048]
[0049] Examples 2-5 below use the same structural formulas and names as in Example 1, and the number-average molecular weights are shown in Table 1.
[0050] Example 2:
[0051] (1) Mix 267.5g of purified terephthalic acid, 132.5g of isophthalic acid (accounting for 25% of the total polyester), 400g of 1,4-butanediol, and 50μg / g of tetrabutyl titanate (calculated as titanium element) and slurry them. Add the mixture to the reaction vessel. The esterification reaction temperature is 220-240℃. After the esterification reaction, the mixture is transferred to the final condensation vessel for polycondensation reaction. The polycondensation temperature is 250-260℃. After reaching the predetermined reaction endpoint, the melt is cooled and granulated to obtain the intrinsic viscosity of the chips: 0.95dL / g.
[0052] (2) Mix 400g of purified terephthalic acid, 240g of ethylene glycol, 92.4g of phenyl ethylene glycol (accounting for 20% of the total polyester), 500μg / g of glycerol, and 150μg / g of antimony glycol (calculated as antimony element) and slurry them. Add the mixture to the reactor. The esterification reaction temperature is 220-260℃. After the esterification reaction, the mixture is transferred to the final condensation reactor for polycondensation reaction. The polycondensation temperature is 270-285℃. When the intrinsic viscosity of the melt reaches 0.85dL / g, add the chips from step 1 to the reactor at a mass ratio of 25%. Continue the reaction for 0.5 hours, cool the melt, and granulate it to obtain amorphous low-temperature resistant composite chips with an intrinsic viscosity of 0.90dL / g.
[0053]
[0054] Example 3:
[0055] (1) Mix 240g of purified terephthalic acid, 159g of isophthalic acid (accounting for 30% of the total polyester), 400g of 1,4-butanediol, and 80μg / g of tetrabutyl titanate (calculated as titanium element) and slurry them. Add the mixture to the reaction vessel. The esterification reaction temperature is 220-250℃. After the esterification reaction, the mixture is transferred to the final condensation vessel for polycondensation reaction. The polycondensation temperature is 250-260℃. After reaching the predetermined reaction endpoint, the melt is cooled and granulated to obtain the intrinsic viscosity of the chips: 1.0dL / g.
[0056] (2) Mix 400g of purified terephthalic acid, 240g of ethylene glycol, 69.3g of phenyl ethylene glycol (accounting for 15% of the total polyester), glycerol, and 5μg / g of tetrabutyl titanate (calculated as titanium element) and slurry them. Add the mixture to the reactor. The esterification reaction temperature is 220-260℃. After the esterification reaction, the mixture is transferred to the final condensation reactor for polycondensation reaction. The polycondensation temperature is 270-285℃. When the intrinsic viscosity of the melt reaches 0.75dL / g, add the chips from step 1 to the reactor at a mass ratio of 15%. Continue the reaction for 0.5 hours, cool the melt, and granulate it to obtain amorphous low-temperature resistant composite chips with an intrinsic viscosity of 0.80dL / g.
[0057]
[0058] Example 4:
[0059] (1) Mix 267.5g of purified terephthalic acid, 132.5g of isophthalic acid (accounting for 25% of the total polyester), 400g of 1,4-butanediol, and 100μg / g of tetrabutyl titanate (calculated as titanium element) and slurry them. Add the mixture to the reaction vessel. The esterification reaction temperature is 220-240℃. After the esterification reaction, the mixture is transferred to the final condensation vessel for polycondensation reaction. The polycondensation temperature is 250-260℃. After reaching the predetermined reaction endpoint, the melt is cooled and granulated to obtain the intrinsic viscosity of the chips: 0.95dL / g.
[0060] (2) Mix 400g of purified terephthalic acid, 240g of ethylene glycol, 83.2g of phenylethylene glycol (accounting for 18% of the total polyester), 46.2g of 1,4-cyclohexanediol, 800μg / g of trimethylolpropane, 5μg / g of tetrabutyl titanate (calculated as titanium element), and 100μg / g of germanium dioxide into a pulp, add it to the reactor, and esterify at a temperature of 220-260℃. After esterification, it enters the final condensation reactor for polycondensation at a temperature of 270-285℃. When the intrinsic viscosity of the melt reaches 0.70dL / g, add the chips from step 1 to the reactor at a mass ratio of 20%, continue the reaction for 0.5 hours, cool the melt, granulate it, and obtain amorphous low-temperature resistant composite chips with an intrinsic viscosity of 0.80dL / g.
[0061]
[0062] Example 5:
[0063] (1) Mix 278g of purified terephthalic acid, 122g of isophthalic acid (accounting for 23% of the total polyester), 400g of 1,4-butanediol, and 50μg / g of tetrabutyl titanate (calculated as titanium element) and slurry them. Add the mixture to the reaction vessel. The esterification reaction temperature is 220-240℃. After the esterification reaction, the mixture is transferred to the final condensation vessel for polycondensation reaction. The polycondensation temperature is 250-260℃. After reaching the predetermined reaction endpoint, the melt is cooled and granulated to obtain the intrinsic viscosity of the chips: 0.95dL / g.
[0064] (2) Mix 400g of purified terephthalic acid, 240g of ethylene glycol, 129.4g of phenyl ethylene glycol (accounting for 28% of the total polyester), 400μg / g of trimethylolpropane, and 90μg / g of germanium dioxide (calculated as germanium element) and slurry them. Add the mixture to the reactor. The esterification reaction temperature is 220-260℃. After the esterification reaction, the mixture is transferred to the final condensation reactor for polycondensation reaction. The polycondensation temperature is 270-285℃. When the intrinsic viscosity of the melt reaches 0.70dL / g, add the chips from step 1 to the reactor at a mass ratio of 20%. Continue the reaction for 0.5 hours, cool the melt, and granulate it to obtain amorphous low-temperature resistant composite chips with an intrinsic viscosity of 0.80dL / g.
[0065]
[0066] The slices prepared in the above experiment were dried and then used to prepare standard specimens using a micro injection molding machine. After being frozen at -24℃ for 12 hours, the mechanical properties of the specimens were tested.
[0067] Table 1 Test performance data of experimental samples
[0068]
Claims
1. A method for preparing an amorphous low-temperature resistant polyester composition, characterized in that: The method is as follows: (1) Mix 294g of purified terephthalic acid, 106g of isophthalic acid, 400g of 1,4-butanediol, and 200μg / g of tetrabutyl titanate (calculated as titanium element) and slurry them. Add the mixture to the reaction vessel. The esterification reaction temperature is 220-260℃. After the esterification reaction, the mixture is placed in the final condensation vessel for polycondensation reaction. The polycondensation temperature is 255-265℃. After the predetermined reaction endpoint is reached, the melt is cooled and granulated to obtain the intrinsic viscosity of the chips: 0.80dL / g, and the number average molecular weight is 34528. (2) Mix 400g of purified terephthalic acid, 240g of ethylene glycol, 138.6g of phenyl ethylene glycol, pentaerythritol, and 200μg / g of antimony glycol (calculated as antimony element) and slurry them. Add the mixture to the reactor. The esterification reaction temperature is 220-260℃. After the esterification reaction, the mixture is transferred to the final condensation reactor for polycondensation reaction. The polycondensation temperature is 270-285℃. When the intrinsic viscosity of the melt reaches 0.65 dL / g and the number average molecular weight is 20175, add the slices from step 1 to the reactor at a mass ratio of 10%. Continue the reaction for 0.5 hours, cool the melt, and granulate it to obtain amorphous low-temperature resistant composite slices with an intrinsic viscosity of 0.70 dL / g and a number average molecular weight of 29525.
2. A method for preparing an amorphous low-temperature resistant polyester composition, characterized in that: The method is as follows: (1) Mix 267.5g of purified terephthalic acid, 132.5g of isophthalic acid, 400g of 1,4-butanediol, and 50μg / g of tetrabutyl titanate (calculated as titanium element) and slurry them. Add the mixture to the reaction vessel. The esterification reaction temperature is 220-240℃. After the esterification reaction, the mixture is placed in the final condensation vessel for polycondensation reaction. The polycondensation temperature is 250-260℃. After the predetermined reaction endpoint is reached, the melt is cooled and granulated to obtain the intrinsic viscosity of the chips: 0.95dL / g. (2) Mix 400g of purified terephthalic acid, 240g of ethylene glycol, 92.4g of phenyl ethylene glycol, 500μg / g of glycerol, and 150μg / g of ethylene glycol antimony (calculated as antimony element) and slurry. Add the mixture to the reactor. The esterification reaction temperature is 220-260℃. After the esterification reaction, the mixture is transferred to the final condensation reactor for polycondensation reaction at a temperature of 270-285℃. When the intrinsic viscosity of the melt reaches 0.85 dL / g, add the slices from step 1 to the reactor at a mass ratio of 25%. Continue the reaction for 0.5 hours, cool the melt, and granulate to obtain amorphous low-temperature resistant composite slices with an intrinsic viscosity of 0.90 dL / g.
3. A method for preparing an amorphous low-temperature resistant polyester composition, characterized in that: The method is as follows: (1) Mix 240g of purified terephthalic acid, 159g of isophthalic acid, 400g of 1,4-butanediol, and 80μg / g of tetrabutyl titanate (calculated as titanium element) and slurry them. Add the mixture to the reaction vessel. The esterification reaction temperature is 220-250℃. After the esterification reaction, the mixture is placed in the final condensation vessel for polycondensation reaction. The polycondensation temperature is 250-260℃. After the predetermined reaction endpoint is reached, the melt is cooled and granulated to obtain the intrinsic viscosity of the chips: 1.0dL / g. (2) Mix 400g of purified terephthalic acid, 240g of ethylene glycol, 69.3g of phenyl ethylene glycol, glycerol, and 5μg / g of tetrabutyl titanate (calculated as titanium element) and beat into a slurry. Add the mixture to a reaction vessel. The esterification reaction temperature is 220-260℃. After the esterification reaction, the mixture is placed in a final condensation vessel for polycondensation reaction at a temperature of 270-285℃. When the intrinsic viscosity of the melt reaches 0.75 dL / g, add the slices from step 1 to the reaction vessel at a mass ratio of 15%. Continue the reaction for 0.5 hours, cool the melt, and granulate to obtain amorphous low-temperature resistant composite slices with an intrinsic viscosity of 0.80 dL / g.
4. A method for preparing an amorphous low-temperature resistant polyester composition, characterized in that: The method is as follows: (1) Mix 267.5g of purified terephthalic acid, 132.5g of isophthalic acid, 400g of 1,4-butanediol, and 100μg / g of tetrabutyl titanate (calculated as titanium element) and slurry them. Add the mixture to the reaction vessel. The esterification reaction temperature is 220-240℃. After the esterification reaction, the mixture is placed in the final condensation vessel for polycondensation reaction. The polycondensation temperature is 250-260℃. After the predetermined reaction endpoint is reached, the melt is cooled and granulated to obtain the intrinsic viscosity of the chips: 0.95dL / g. (2) Mix 400g of purified terephthalic acid, 240g of ethylene glycol, 83.2g of phenyl ethylene glycol, 46.2g of 1,4-cyclohexanediol, 800μg / g of trimethylolpropane, 5μg / g of tetrabutyl titanate (calculated as titanium), and 100μg / g of germanium dioxide (calculated as germanium) into a slurry and add it to the reactor. The esterification reaction temperature is 220-260℃. After the esterification reaction, it enters the final condensation reactor for polycondensation reaction. The polycondensation temperature is 270-285℃. When the intrinsic viscosity of the melt reaches 0.70 dL / g, add the slices from step 1 to the reactor at a mass ratio of 20%. Continue the reaction for 0.5 hours, cool the melt, granulate it, and obtain amorphous low-temperature resistant composite slices with an intrinsic viscosity of 0.80 dL / g.
5. A method for preparing an amorphous low-temperature resistant polyester composition, characterized in that: The method is as follows: (1) Mix 278g of purified terephthalic acid, 122g of isophthalic acid, 400g of 1,4-butanediol, and 50μg / g of tetrabutyl titanate (calculated as titanium element) and slurry them. Add the mixture to the reaction vessel. The esterification reaction temperature is 220-240℃. After the esterification reaction, the mixture is placed in the final condensation vessel for polycondensation reaction. The polycondensation temperature is 250-260℃. After the predetermined reaction endpoint is reached, the melt is cooled and granulated to obtain the intrinsic viscosity of the chips: 0.95dL / g. (2) Mix 400g of purified terephthalic acid, 240g of ethylene glycol, 129.4g of phenyl ethylene glycol, 400μg / g of trimethylolpropane, and 90μg / g of germanium dioxide (calculated as germanium element) and slurry them. Add the mixture to the reactor. The esterification reaction temperature is 220-260℃. After the esterification reaction, the mixture is placed in the final condensation reactor for polycondensation reaction. The polycondensation temperature is 270-285℃. When the intrinsic viscosity of the melt reaches 0.70 dL / g, add the slices from step 1 to the reactor at a mass ratio of 20%. Continue the reaction for 0.5 hours, cool the melt, and granulate it to obtain amorphous low-temperature resistant composite slices with an intrinsic viscosity of 0.80 dL / g.
Citation Information
Patent Citations
Low-temperature-resistant biaxially-oriented polyester film and preparation method thereof
CN103042780A
Low-temperature toughened and reinforced PC / PBT (polycarbonate / polybenzothiazole) alloy material and preparation method thereof
CN105255149A
Low-temperature-impact resistant polyester composition and preparation method thereof
CN108034204A
Low-melting point and transparent PET copolyester, its preparation method and application
CN103102473A
Amorphous polyester composition and preparation method and application thereof
CN105778065A